2003
DOI: 10.1046/j.1526-4637.2003.03034.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Unequal Burden of Pain: Confronting Racial and Ethnic Disparities in Pain

Abstract: A B S T R A C TContext. Pain has significant socioeconomic, health, and quality-of-life implications. Racial-and ethnic-based differences in the pain care experience have been described. Racial and ethnic minorities tend to be undertreated for pain when compared with non-Hispanic Whites.Objectives. To provide health care providers, researchers, health care policy analysts, government officials, patients, and the general public with pertinent evidence regarding differences in pain perception, assessment, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

43
766
10
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,047 publications
(827 citation statements)
references
References 169 publications
(187 reference statements)
43
766
10
8
Order By: Relevance
“…Whether he receives the standard of care that he expects, however, is likely contingent on his race/ethnicity. Prior research suggests that if he is black, then his pain will likely be underestimated and undertreated compared with if he is white (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The present work investigates one potential factor associated with this racial bias.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Whether he receives the standard of care that he expects, however, is likely contingent on his race/ethnicity. Prior research suggests that if he is black, then his pain will likely be underestimated and undertreated compared with if he is white (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The present work investigates one potential factor associated with this racial bias.…”
mentioning
confidence: 94%
“…The first possibility is that physicians recognize black patients' pain, but do not to treat it, perhaps due to concerns about noncompliance or access to health care (7,8). The second possibility is that physicians do not recognize black patients' pain in the first place, and thus cannot treat it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant gaps in the literature about the pain experiences of persons of racial minorities (GREEN et al, 2003) and there is also growing interest in understanding the influence of race and ethnicity on the experience of pain (EDWARDS et al, 2001b;EDWARDS;KEEFE, 2001). Investigators have recently indicated that African Americans report greater levels of pain than whites for conditions such as glaucoma, AIDS, migraine headache, jaw pain, postoperative pain, myofascial pain, angina pectoris, joint pain, nonspecific daily pain and arthritis (EDWARDS et al, 2001).…”
Section: Pain Discomfort and Racementioning
confidence: 99%
“…Overall, little is known about what influences differences in pain-related quality of life and further investigation is needed to understand racial differences in pain (GREEN et al, 2003).…”
Section: Pain Discomfort and Racementioning
confidence: 99%